Pengaruh Metode Peer Education terhadap Perilaku Pencegahan Demam Berdarah Dengue (DBD) Dengan Pendekatan Health Promotion Model (HPM) Di SMPN 2 Bungku Tengah Kabupaten Morowali - Yusriani Yusriani; Sundari Sundari; Mega Aulia (Universitas Pahlawan Tuanku Tambusai, 2025)
The tropical geographical conditions of Morowali with a long rainy season greatly support the breeding of Aedes aegypti mosquitoes, a factor causing dengue fever (DHF). Therefore, Morowali requires a more integrated approach and involves the community directly in prevention efforts, especially with more innovative methods that can reach various groups such as the peer education method. The purpose of this study was to determine the effect of the peer education method with the Health Promotion Model (HPM) approach on changes in knowledge and behavior in preventing Dengue Fever (DHF) before and after. This study used a quantitative research type with a quasi-experiment two-group method. The population was 120 students with a sample size of 60 people. Samples were taken randomly using the random sampling method. Data collection used a closed questionnaire. The data analysis technique used the Wilcoxon test. The results of the study showed a mean rank value of 90.37, meaning that peer education has a large influence on behavioral changes, while knowledge has a mean rank value of 86.73 on preventing Dengue Fever (DHF). The significance value of 0.000 <0.05 indicates that Ha is accepted and Ho is rejected so that there is a significant influence between the peer education method and the Health Promotion Model (HPM) approach on changes in behavior in preventing Dengue Hemorrhagic Fever (DHF). This study shows that health education involving students as agents of change is effective in improving student behavior in preventing DHF.